"All the research says": manufactured consensus and the burden of proof in the racialized police violence controversy. (4th May 2022) - Earle, Chris S.
Abstract: This article reconstructs and analyzes the argument strategies used by right-wing public intellectuals, journalists, and political figures to delegitimize the controversy over racialized police violence. I demonstrate how right-wing advocates aim to shift the issue to the technical sphere, claiming to represent an expert consensus and depicting antiracist advocates as misunderstanding, if not intentionally misusing, technical data. This case provides a rich opportunity to deepen rhetoric and argument study of, first, how advocates disguise racist and post-racial discourses in the terms of technical expertise, and, second, how the burden of proof is assigned and negotiated within racial controversies. Claiming to represent an expert consensus would seem to carry a much higher burden of proof than would amplifying technical uncertainty. I argue, however, that defenders of the police mitigate this burden through heavy reliance on argument from ignorance, insinuating that the supposed lack of evidence of officer bias means that police use of lethal force must be racially fair.